THE INTERRELATIONSHIP BETWEEN INNOVATIVE MARKETING AND BRAND EQUITY, AN APPLIED: STUDY THE GENERAL COMPANY FOR SOUTHERN CEMENT / AL-KUFA CEMENT FACTORY - Muhammad Najm Abd; Salima Hadi Musa; Prof. Dr. Hamed Kazem Meteb Al Shahbawi (Scholar Express Journals, 2023)
The research focused on innovative marketing(IM) as an independent variable with dimensions of innovative promotion(IP) , innovation Price(IR) Product innovation, (distribution, and brand equity) as a dependent variable with its dimensions of awareness Brand loyalty, brand loyalty, brand association and brand image) to determine the relationship between (IM) , trademark ownership rights, the research was tested in a laboratory Kufa cement, the study population was (1132) workers, (287) questionnaires were distributed, 41 were excluded An invalid questionnaire, leaving 246 questionnaires that were actually used in statistical analysis, they were representative The sample is 25% of society. The researchers aimed to investigate five respondents for each paragraph. It was included The research hypothesis of the correlation relationship, and the statistical program (24.SPSS.V) was used to analyze the results .The research reached the acceptance of all the hypotheses, and the research reached a set of theoretical conclusions And applied, among them, is that foundations of (IM) are closely related to rethinking , working on Continuously developing companies’ work, brand is an indispensable foundation in Tarsi The company's competitive position The study presented a set of recommendations, including stimulating human resource that Contributes to increasing marketing and innovative operations.
Keywords: innovative marketing; brand equity